Strong Exchange Coupling in a Trimetallic Radical‐Bridged Cobalt(II)‐Hexaazatrinaphthylene Complex. (21st March 2016) - Moilanen, Jani O.; Chilton, Nicholas F.; Day, Benjamin M.; Pugh, Thomas; Layfield, Richard A.
Abstract: Reducing hexaazatrinaphthylene (HAN) with potassium in the presence of 18‐c‐6 produces [{K(18‐c‐6)}HAN], which contains the S=1/2 radical [HAN] .− . The [HAN] .− radical can be transferred to the cobalt(II) amide [Co{N(SiMe3 )2 }2 ], forming [K(18‐c‐6)][(HAN){Co(N′′)2 }3 ]; magnetic measurements on this compound reveal an S=4 spin system with strong cobalt–ligand antiferromagnetic exchange and J≈−290 cm −1 (−2 J formalism). In contrast, the Co II centres in the unreduced analogue [(HAN){Co(N′′)2 }3 ] are weakly coupled (J≈−4.4 cm −1 ). The finding that [HAN] .− can be synthesized as a stable salt and transferred to cobalt introduces potential new routes to magnetic materials based on strongly coupled, triangular HAN building blocks. Abstract : Das [HAN] .− ‐Radikalanion (siehe Schema, links) wurde als stabiles Kaliumsalz synthetisiert und in intakter Form an Co II ‐Zentren koordiniert. Das entstehende Komplexanion [{(HAN){Co(N′′)2 }3 ] − ist einer von wenigen bekannten radikalverbrückten Dreikernkomplexen, und es zeigt einen sehr starken antiferromagnetischen Austausch zwischen den Co II ‐Ionen und dem redoxaktiven Liganden.